ANALISIS MAKNA DALAM GEGURITAN IKI GURITE SEPI KARYA SURTIKANTI (SUATU KAJIAN SEMIOTIKA RIFFATERRE) - Ayuni Diah Melani; Laelatur Rosyidah; Dhiya Restu Putra; Alfan Muhyar Faza (Universitas Sebelas Maret, 2021)
This study aims to describe a sign and implied meaning in Surtikanti’s Geguritan Iki Gurite Sepi poetry. The approach used in this study is a semiotic approach based on Michael Riffaterre's model. Based on Riffaterre's semiotic approach, the data in this study were analyzed by: 1) Heuristic reading; 2) Hermeneutic Reading; 3) Indirectness of expression; 4) Matrix, model, and variant of poetry; 5) Hypogram. The method used is descriptive qualitative which produces descriptive qualitative data in the form of words, phrases, and sentences contained in poetry. The results of this study indicate that the semiotics used in the study of Javanese poetry or geguritan entitled Geguritan iki, gurite sepi by Surtikanti's has markers and signifiers in it.